2021
DOI: 10.1016/j.omtn.2020.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Association of clock-like mutational signature with immune checkpoint inhibitor outcome in patients with melanoma and NSCLC

Abstract: Immune checkpoint inhibitor (ICI) therapy has achieved remarkable clinical benefit in melanoma and non-small cell lung cancer (NSCLC). Tumor mutational signatures are the fingerprints of endogenous and exogenous factors that have acted throughout tumorigenesis and heterogeneity; however, their association with immune response in ICI-treated samples remains unclear. Here, we leveraged whole-exome sequencing (WES)-based mutational profiles combined with clinicopathologic characteristics from melanoma and NSCLC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 56 publications
4
29
2
Order By: Relevance
“… 12 , 13 , 14 Overcoming immunotherapy resistance is challenging because of the complex and dynamic interplay among malignant cells and the immune defense system. 15 , 16 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 Overcoming immunotherapy resistance is challenging because of the complex and dynamic interplay among malignant cells and the immune defense system. 15 , 16 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that high copy number, aneuploidy, and HRD-associated scores inversely correlate with tumor immune response [28][29][30] , and negative results in a recent clinical trial in ovarian cancer where half of the tumors showed HRD 31,32 suggest that HRD-related signatures are unlikely to be associated with high sensitivity to ICIs. Aging-related (clock-like) mutational signatures are reported to be associated with lower immune activity in melanoma and non-small cell lung cancer treated with ICI 9,33 . Since many age-related gene mutations also occur in non-tumor cells 34 , they may be related to immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Aging-related (clock-like) mutational signatures are reported to be associated with lower immune activity in melanoma and non-small cell lung cancer treated with ICI 9,32 . Since many age-related gene mutations also occur in non-tumor cells 33 , they may be related to immune tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown that the clock-like mutational signature affects the outcome of ICB in patients with specific cancers. 64 This finding prompted us to extract somatic mutational profiles from TCGA datasets and annotated the clock-like signature against the Catalog of Somatic Mutations in Cancer (COSMIC) 65 (Figure S7B-D). Then, we stratified the LUAD samples into clock-like or non-clock-like subtypes in terms of mutational signature activities.…”
Section: Construction Of a Circadian-related Model For Predicting Res...mentioning
confidence: 99%